Intolerance of uncertainty, social anxiety, and generalized anxiety: Differences by diagnosis and symptoms. (June 2017) - Counsell, Alyssa; Furtado, Melissa; Iorio, Christina; Anand, Leena; Canzonieri, Alexandra; Fine, Alexa; Fotinos, Kathryn; Epstein, Irvin; Katzman, Martin A.
Abstract: Research suggests that Intolerance of Uncertainty (IU) is related to the severity of suffering in Generalized Anxiety Disorder (GAD). However, its role in Social Anxiety Disorder (SAD) has not been extensively studied. This study examines IU in a clinical sample of 248 individuals referred to a tertiary care clinic. Few individuals had a diagnosis of pure SAD or pure GAD, but we examined differences of IU scores by diagnostic category. We further examined the relationships between IU scores, social anxiety scores, and worry through a structural equation model. We found that diagnostic category (SAD versus GAD) accounted for little variability in IU scores, but IU scores were strongly related to symptoms of both GAD and SAD. Results highlight that IU is related to both social anxiety and worry; however aspects of IU associated with being unable to act or avoiding uncertainty are more strongly associated with SAD symptoms, whereas aspects of IU more associated with general stress and perceiving uncertainty as unfair are more strongly associated with GAD symptoms. Our results suggest that IU is an important concept for both social anxiety and generalized anxiety, however the relationship between IU and symptoms of these disorders manifests differently. Highlights: Association between Intolerance of Uncertainty and Social Anxiety Disorder. Intolerance of Uncertainty impacts individuals with SAD and GAD in different ways. IU items focused on causing an inability to act were more predictive of SAD. IU items focused on associated stress were more predictive of GAD.